Contributions to the phytotherapies of digestive disorders: Traditional knowledge and cultural drivers of Manoor Valley, Northern Pakistan. (4th November 2016) - Rahman, Inayat Ur; Ijaz, Farhana; Afzal, Aftab; Iqbal, Zafar; Ali, Niaz; Khan, Shujaul Mulk
Abstract: Ethno pharmacological relevance: Ethno medicinal traditional knowledge regarding the uses of indigenous medicinal plants used for various human digestive disorders are mostly known to the elder community members. As the young generation is not much aware about such vital traditional medicinal practice because they rely on elders. Aim of study: To document, accumulate and widely disseminate the massive indigenous knowledge of century's practiced therapeutic uses of medicinal plants by the local people living in this remote area. Materials and methods: A total of 63 local inhabitants (39 males and 24 females) were interviewed through a structured questionnaire. The data obtained were quantitatively analyzed through the use value (UVi ), fidelity level index (FL%) and relative frequency citations (RFCs), consensus index (CI%) and informant consensus factor (FIC ). For novel uses all the plants were checked with previously published articles on same disease by analyzing through Jaccard index (JI) and Sorensen's similarity index (QS). Plants specimen were preserved, mounted and labeled on the herbarium sheets, cataloged and deposited with voucher numbers in Hazara University Herbarium, Mansehra, Pakistan (HUP). Results: 44 plant species belonging to 44 genera and 28 families were documented in the current study. These medicinal plant species were used commonly as an ethno medicine against 26 various digestive disorders out of which most frequently occurred are; stomach ache, diarrhea, indigestion, constipation and inflammation etc. Herbaceous plant species were the dominant among plants studied which were 64% of the total plants, followed by trees (20%) and shrubs (16%). Lamiaceae was the leading family among collected medicinal plant species (13.6%). Maximum medicinal plant species were used for treatment of stomach ache (11.7%), diarrhea and indigestion (10.9% each). Most widely used parts were leaves (41% citations), fruit and whole plant (12% citations each) for medication of various digestive problems by the traditional drivers. Dominated medicinal plants with most use values were Ficus carica having (UVi =0.90) and Trifolium repens (UVi =0.84). Based on the RFC values, the most cited medicinal plant species by the traditional drivers were Ficus carica (0.43) and Berberis lycium (0.41), while most respondents percentage was noticed for same plant species calculated through consensus index (CI%=42.9% and 41.3%) respectively. The medicinal plant species with highest fidelity level was of Grewia optiva, Juglans regia and Sorbaria tomentosa each cited 100% for anthelmintic, easy digestion and Diarrhea respectively. Due to representation by only single medicinal plant taxa ( N t=1), the digestive diseases viz. cholera, colon cancer, emetic, internal injuries, kill microorganisms, Soothing, tumor and urine suppression had maximum FIC value. The analytical result reveals that 57% of medicinal plant species were reported for the first time regarding their uses. new medicinal uses of Anaphalis contorta, Caltha palustris, Pinus wallichiana, Plantago himalaica were recorded for the first time from Pakistan and Aralia cachemirica, Bupleurum longicaule, Pleurospermum stellatum, Potentilla argentea and Juglans regia across the globe for currently reported medicinal uses. Besides this, all the mentioned plant species were reported for the first time for digestive disorders from Manoor Valley as no single study up-till now has been conducted ethno medicinally. Conclusion: The present study revealed the importance to document and launch list of all the possible plants that are used in traditional medicinal practices against digestive disorders in the unexplored study area and to show the important medicinal plants for future biological, phytochemical and pharmacological experimentation regarding digestive problems. Graphical abstract: